O DIREITO HUMANO À MORADIA NO CONTEXTO PANDÊMICO: A DESOCUPAÇÃO VIOLENTA DO QUILOMBO CAMPO GRANDE NA PERCEPÇÃO DOS CONFLITOS SOCIAIS. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The year 2020 is marked by the sad and rapid expansion of the covid-19 pandemic. In Brazil, in the midst of chaos, while some have adequate housing to protect themselves, others do not and others still have been violently evicted from their homes. Residential isolation at this time is the safest means of protection and, in compliance with the court order, the State vacated the so-called “Quilombo Campo Grande”, in the interior of Minas Gerais, which was occupied by the Landless Workers Movement-MST for years, causing great astonishment and commotion for the form and the context in which the eviction occurred. Thus, this research focuses on analyzing the violent eviction in that place with the aggravating context. The study of social conflicts from a Marxist perspective, which trigger social movements allied to housing issues, are essential for understanding the theme. For that, the methodology used will be the literary review with a survey both doctrinal and scientific and journalistic articles.